2022
DOI: 10.3390/w14142188
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Networks Reveal the Structure of Water Microbial Communities in Kalamaili Mountain Ungulate Nature Reserve

Abstract: Water microorganisms contribute to the key components of ecosystems in dryland waters, which are extremely important for wildlife. However, the distribution patterns of water microbes across different basal water sources are still largely unknown. This study was conducted to compare microorganisms in the water bodies of different types of water sources in the Kalamaili Mountain Ungulate Nature Reserve in China. Bioinformatic analysis revealed that the undirected microbial co-existence network consisted of 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…[41] found that the standard, unmodified cement in artificial reefs showed lower biodiversity than the other two types of cement, which contained bioactive materials. The lower microbial diversity on its surface indicates the slightly toxic nature of this cement to marine bacteria, as previously shown for bacteria in groundwater stored in concrete or earthen ponds, the former being lower in diversity and abundance [114]. Indeed, concrete has been described as having especially deleterious consequences on biodiversity in all aquatic ecosystems [115]; this concords with research suggesting that a relatively mature microbial biofilm on concrete in the marine environment is somewhat generic, differing little from normal structural concrete composition [39][40][41].…”
Section: Artificial Reefs: a Special Casesupporting
confidence: 61%
“…[41] found that the standard, unmodified cement in artificial reefs showed lower biodiversity than the other two types of cement, which contained bioactive materials. The lower microbial diversity on its surface indicates the slightly toxic nature of this cement to marine bacteria, as previously shown for bacteria in groundwater stored in concrete or earthen ponds, the former being lower in diversity and abundance [114]. Indeed, concrete has been described as having especially deleterious consequences on biodiversity in all aquatic ecosystems [115]; this concords with research suggesting that a relatively mature microbial biofilm on concrete in the marine environment is somewhat generic, differing little from normal structural concrete composition [39][40][41].…”
Section: Artificial Reefs: a Special Casesupporting
confidence: 61%